Relationships between Metacognition, Self-efficacy and Self-regulation in Learning - Rosa Cera; Michela Mancini; Alessandro Antonietti (LED Edizioni Universitarie, 2013)
The ability to manage study activities by themselves is one of the educational goals that learners should achieve at the end of secondary school. Self-regulation, however, includes a variety of metacognitive issues. Firstly, self-regulated students should be aware of the mental processes they rely on when performing cognitive tasks, of the degree of autonomy they are allowed in managing study activities and of how effective they are in facing school demands. Secondly, students should be able to plan and monitor study activities strategically. Thirdly, students should identify the kind of learning which is expected to be reached. A sample of 130 students were administered 5 different of questionnaires designed to investigate the metacognitive awareness (MAI: Schraw & Dennison, 1994), the perception of autonomy in school learning (AILI: Elishout-Mohr, Van Daalen-Kapteijns, & Meijer, 2004), the sense of self-efficacy (Adaptive Self-Efficacy Scale: Sibilia, Schwarzer, & Jerusalem, 1995), the attitudes of study strategies (LASSI: Weinstein & Palmer, 2002), and the questionnaire on the conceptions of learning (QAPCOL: Pérez-Tello, Antonietti, Liverta-Sempio, & Marchetti, 2002). Results revealed that self-regulated learning is linked to metacognitive skills such as planning, monitoring, evaluation and concentration. In addition, the knowledge and the proper use of learning strategies - such as the selection of the main ideas in a text - constitutes a related set of metacognitive skills. Finally, it was found that the acquisition of metacognitive knowledge, skills and attitudes is linked to autonomy in the study and to self-efficacy.